Determination of antioxidant in tomato (solanum lycopersicum l.) using ferric reducing antioxidant power (frap) assay / Nor Syafiqah Zakaria - Zakaria, Nor Syafiqah (Faculty Of Applied Sciences, 2017)
Tomatoes (Solanum Lycopersicum L) is one of the most consumed fruits in the world that plays an important role in disease prevention. The purposes of this study were to determine the amount antioxidant of tomato and the effect of temperature and cook duration on the antioxidant of tomatoes using Ferric Reducing Antioxidant Power (FRAP) assay. UV-Vis spectrophotometer was used in this study to analyze tomato sample. The antioxidant capacity of tomatoes which was 169.93±0.92 µM Fe(II)/mL. For temperature study, tomatoes exhibited the greatest antioxidant at 100°C and the lowest amount of antioxidant at room temperature. Thus, it could be concluded that, the optimum temperature for the antioxidant extraction in tomatoes was 100°C. Besides, for cook duration study, it showed increasing of the antioxidant capacity from 5 minutes to 15 minutes before dropped at 20 minutes. Thus, most suitable cook duration of tomato in order to gain a greatest amount of antioxidant was 15 minute.